Neuronal Plasticity-Dependent Paradigm and Young Plasma Treatment Prevent Synaptic and Motor Deficit in a Rett Syndrome Mouse Model - Sofía Espinoza; Camila Navia; Rodrigo F. Torres; Nuria Llontop; Verónica Valladares; Cristina Silva; Ariel Vivero; Exequiel Novoa-Padilla; Jessica Soto-Covasich; Jessica Mella; Ricardo Kouro; Sharin Valdivia; et al. (Biomolecules)
Classical Rett syndrome (RTT) is a neurodevelopmental disorder caused by mutations in the MECP2 gene, resulting in a devastating phenotype associated with a lack of gene expression control. Mouse models lacking Mecp2 expression with an RTT-like phenotype have been developed to advance therapeutic alternatives. Environmental enrichment (EE) attenuates RTT symptoms in patients and mouse models. However, the mechanisms underlying the effects of EE on RTT have not been fully elucidated. We housed male hemizygous Mecp2-null (Mecp2-/y) and wild-type mice in specially conditioned cages to enhance sensory, cognitive, social, and motor stimulation. EE attenuated the progression of the RTT phenotype by preserving neuronal cytoarchitecture and neural plasticity markers. Furthermore, EE ameliorated defects in neuromuscular junction organization and restored the motor deficit of Mecp2-/y mice. Treatment with plasma from young WT mice was used to assess whether the increased activity could modify plasma components, mimicking the benefits of EE in Mecp2-/y. Plasma treatment attenuated the RTT phenotype by improving neurological markers, suggesting that peripheral signals of mice with normal motor function have the potential to reactivate dormant neurodevelopment in RTT mice. These findings demonstrate how EE and treatment with young plasma ameliorate RTT-like phenotype in mice, opening new therapeutical approaches for RTT patients.